Remote Camera For Android Based Smartphones Installed On The Syma X8HG Drone - Wintolo, Hero; Sudaryanto, Sudaryanto; Pramudito, Christoporus Galih (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The camera on the smartphone was basically to take pictures or video with equivalent quality digital camera or video recorder. The camera on the smartphone lies in two different locations, first place the rear side and the second being in front. Drone Syma x8hg who used to fly a smartphone for the shooting process is controlled from the laptop software, maximum range 80 meters from the drones by remote control. Software on Android devices and laptops must first diinstalisasi so both devices can be connected to the web server of the provider to process images from a drone Syma x8hg, the two devices must have a network connection provider respectively. Results from testing the smartphone camera carried by a flying drone can be controlled for filming with the distance is affected by the strength of the signal from the service providers internet connection, while the height is limited by the strength of the signal between the drone with remote control.